A thermodynamic tank model for studying the effect of higher hydrocarbons on natural gas storage in metal–organic frameworks1. Issue 5 (6th May 2015) - Zhang, Hongda; Deria, Pravas; Farha, Omar K.; Hupp, Joseph T.; Snurr, Randall Q.
<x xml:space="preserve">Abstract</x> A thermodynamic model was developed to evaluate the cyclic performance of metal–organic frameworks in adsorbing natural gas containing methane and higher hydrocarbons in a vehicle tank.